A 1‐year prospective analysis of injuries in amateur and elite fistball. Issue 3 (12th September 2013) - Runer, A.; Runer, F.; Neunhäuserer, D.; Ring‐Dimitriou, S.; Resch, H.; Moroder, P.
<x xml:space="preserve">Abstract</x> The purpose of this study was to examine the incidence and mechanisms of acute injuries in the sport of fistball. No scientific studies on injury characteristics have yet been conducted in this traditional sport game. The study was conducted prospectively over the course of 12 months. During a total of 40.308 h of sport‐specific exposure, 240 players reported 492 injuries, representing an overall injury rate of 12.2 injuries/1000 h of exposure. Most injuries were classified as bagatelle injuries (67.8%). The majority of the injuries were located in the knee (23.5%) followed by the elbow (11.9%) and the hip (11.5%). Ankle injuries resulted in the longest impairment from sports participation. The most common types of injury were abrasions (38.2%), contusions (21.1%), distortions (7.5%) and muscle strains (6.9%). Wrong or insufficient equipment (15.0%) was the most commonly mentioned causes of injury. The data indicate that the injury risk in fistball is rather high; however, the sport should not be considered a high‐risk sport because most of the injuries are slight and do not prevent the players from training or competition. Injury prevention strategies should include the development of fistball‐specific protective equipment with focus on the knee and elbow joint.